International trade in agricultural products in Poland within 2007-2011 - Iwona Soczewka; Agnieszka Ginter (Journal of Agribusiness and Rural Development, 2013)
The aim of the paper is in-depth analysis of changes in the values and directions of Polish international trade in agri-food products in 2007-2011, a period of global crisis. The study takes into account the political and economic conditions existing in Poland and in the world, and having an impact on our foreign trade turnover. Based on the analysis of statistical data it was found that the Polish agri-food sector since 2003 has been characterised by a gradual increase and improvement of the results of foreign trade, but the global crisis has stunted the dynamics. In the geographical structure of both export and import of agri-food products predominate the EU countries, but as the study revealed, in export the share of the CIS countries and developing countries has been steadily increasing.